Sistem Pakar Pendeteksi Penyakit Pada Tanaman Alpukat Menggunakan Metode Certainy Factor Berbasis Website - Hidayat; Satrianansyah; Zulfauzi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Avocado fruit or often called avocado in Latin originates from Central America, namely Mexico, Peru and Venezuela, and has spread to various countries as far as Southeast Asia, including Indonesia. There are three main types of avocado species, native to Mexico, the Caribbean and Guatemala. The three versions differ in shell composition, fruit size, fat content, taste, disease resistance and environmental adaptations. These different varieties are widespread in various regions in Indonesia. Lubuklinggau City is one of the avocado-producing areas in 2020. Lubuklinggau City produces 910 Avocado Kuitals. Farmers face several obstacles in increasing avocado production, mainly due to diseases that attack avocado plants. Farmers face various problems, namely the lack of knowledge about symptoms, causes, pests and diseases and how to control pests and diseases in avocado plants. And there is no system that can be used by avocado farmers to detect or diagnose diseases in avocado plants so that farmers can find solutions or treatments for existing diseases. To overcome the current problems, an application is needed to diagnose avocado plant diseases, one of which is by using an expert system. An expert system is a computer program that mimics the expertise of an expert. The method that is often used in expert systems is the certainty factor method. Certainty factor method, this method is a method to show the uncertainty of the expert's thinking, to correct it, certainty is usually used to describe the level of expert confidence in the problem at hand. The results of this study will help solve problems related to the diagnosis and treatment of avocado plant diseases.